Pathogenesis and treatment of neuropsychiatric systemic lupus erythematosus: A review - Liu, Yuhong; Tu, Zhihua; Zhang, Xi; Du, Keqian; Xie, Zhengquan; Lin, Zhiming (Frontiers in Cell and Developmental Biology, 2022)
Systemic lupus erythematosus (SLE) is an autoimmune inflammatory disease with a complex pathogenesis. Neuropsychiatric systemic lupus erythematosus (NPSLE) is a serious complication of SLE that involves the nervous system and produces neurological or psychiatric symptoms. After decades of research, it is now believed that the diverse clinical manifestations of NPSLE are associated with intricate mechanisms, and that genetic factors, blood-brain barrier dysfunction, vascular lesions, multiple autoimmune antibodies, cytokines, and neuronal cell death may all contribute to the development of NPSLE. The complexity and diversity of NPSLE manifestations and the clinical overlap with other related neurological or psychiatric disorders make its accurate diagnosis difficult and time-consuming. Therefore, in this review, we describe the known pathogenesis and potential causative factors of NPSLE and briefly outline its treatment that may help in the diagnosis and treatment of NPSLE.